Stress-Strain State Analyses of the Composite Steel and Concrete Grid Structure - Gasii, Grygorii; Hasii, Olena (International Journal of Sustainable Construction Engineering and Technology, 2023)
The study provides developing a method of the tress-strain state analyses of the composite steel and concrete grid structure, the main assumptions, and analysis of the geometry of the structure, the elementary states of equilibrium of the structures are considered, and the systems of determining equations are solved. The method of the stress-strain state analyses is proposed to be performed using the basic provisions of the technical theory of calculating thin shells. The method provides obtaining and solving the design models, and the equations needed for calculating the bearing capacity of the members of the composite steel and concrete grid structure. In particular, the method is for determining the essential area of the cross-section of the prestressed reinforcement, as well as to determine the forces that are acted in the composite steel and concrete structure. In general, the method provides designing the composite steel and concrete structure, determining the bearing capacity, and selecting the necessary dimensions of the structural elements of the composite steel and concrete structure.